Spatial configuration between zoning area in simple residential houses at limited space post pandemic situation - Hidayatullah, Ardiansyah Rahmat; Nor Eeda Haji Ali, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The prolonged COVID19 pandemic situation that began in 2019 has become a phenomenon that affects many aspects of life, including habits, behavior, and space requirements in residential facilities. A form of change that can feel is increasing or decreasing space based on its zoning. Both public and private areas have their roles in building function. Even the spatial preferences are transformed spatially. This need is undoubtedly a particular concern that needs to be considered in its approach to a dwelling with limited land. This study analyzes the forms of changes in space requirements in public, semi-public, semi-private, service, and private areas in a residential facility on limited land to produce recommendations for processing spatial configurations between areas. The research was conducted through an exploratory, descriptive approach by identifying user needs before and after the pandemic and then reviewing the relevance of the theory of spatial relations. In addition, experimental methods are used to find and respond to the utilization and division of space in dwellings on limited land. The need for housing, especially on limited land, remains a top priority for people with middle to lower economic levels. Efforts to fulfill this can only be achieved by housing ownership with limited land. However, this is contrary to the availability of land whose space capacity is not sufficient to meet the needs. The architectural solution is : vertical development strategy, create public awareness to have a healthy dwelling becomes an obligation, adjusting economic value preferences or expenses need to be invested wisely by considering appropriate building development strategies while maintaining health, function, and aesthetics, and Spatial configuration in responding to a pandemic is essential, namely through an organization or spatial arrangement. With the processing that is carried out, it can create a more effective and efficient spatial organization and provide a better quality of life, health, and psychology.